Intranasal corticosteroid use in patients with allergic rhinitis - Svetlana V. Starostina; Alexey V. Toldanov (ZAO "Consilium Medicum", 2021)
Allergic rhinitis (AR) is one of the most common diseases in the world, which is based on IgE-mediated inflammation that develops after exposure to various allergens. About 40% of people suffer from the same or other allergic diseases, every third inhabitant of the Earth has symptoms of AR and every tenth has bronchial asthma. According to the ARIA classification, ARs are divided: by the nature of the flow, by the severity of the flow and by the stage of the flow; for symptoms, the proposed therapy, consisting of sequential steps. Groups of drugs include: systemic or topical blockers of histamine H1 receptors, intranasal and systemic corticosteroids, mast cell stabilizers (intranasal cromones), M-antagonists, antagonists of leukotriene receptors. Medicines do not give a lasting effect after their cancellation, therefore, with persistent AR, treatment should be prolonged; methods of application more often oral or intranasal. The advantages of the pharmacological antiallergic effect of InHCS are the simultaneous inhibition of both the early and late phases of the allergic response and the inhibition of all AR symptoms. The advantage of InHCS over oral administration is the minimal risk of developing systemic side effects against the background of the creation of adequate concentrations of the substance in the nasal mucosa, which allows to control the symptoms of AR. Based on data from a number of studies, the advantages of intrasal corticosteroids for AR, in particular fluticasone propionate, are used.